1980
DOI: 10.3758/bf03334473
|View full text |Cite
|
Sign up to set email alerts
|

Is there sign-tracking in aversive conditioning?

Abstract: The present experiment studied the approach-withdrawal behavior of rats relative to conditioned stimuli (CS) that were paired with shock (paired), paired with absence of shock (unpaired), or that bore no temporal relation with shock (random). In the paired condition, the rats equally divided their time between the side of a tilt cage on which the CS was presented and the other side. In the random condition, the rats displayed a preference for the CS side. In the unpaired condition, the rats displayed a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although Karpicke, Christoph, Peterson, and Hearst (1977) obtained indirect evidence for this kind of sign-tracking, they did not measure the positions of their rats with respect to the stimuli. Using direct measurement of position, Bartter and Masterson (1980) found evidence for aversive sign-tracking, as defined above; however, the amounts of approach and avoidance were small compared to amounts commonly observed in the appetitive case. Bartter and Masterson suggested that an analogy based on stimulus-unconditioned stimulus relationships might be inferior to one based on stimulus-incentive relationships.…”
Section: Discussionmentioning
confidence: 79%
“…Although Karpicke, Christoph, Peterson, and Hearst (1977) obtained indirect evidence for this kind of sign-tracking, they did not measure the positions of their rats with respect to the stimuli. Using direct measurement of position, Bartter and Masterson (1980) found evidence for aversive sign-tracking, as defined above; however, the amounts of approach and avoidance were small compared to amounts commonly observed in the appetitive case. Bartter and Masterson suggested that an analogy based on stimulus-unconditioned stimulus relationships might be inferior to one based on stimulus-incentive relationships.…”
Section: Discussionmentioning
confidence: 79%
“…Evidence also supports the complementary effect involved in approaching responses elicited by cues that predict the omission of an aversive stimulus (see Leclerc & Reberg, 1980). However, some attempts to reproduce such a phenomenon in the aversive domain have not been entirely successful (e.g., Bartter & Masterson, 1980; Nieto & Boakes, 1987).…”
Section: Conditioned Inhibition: the Cumulative Effect Of Inhibitory ...mentioning
confidence: 99%